(untitled) (CIPEEX, 2025)
Introduction: Occupational accidents related to exposure to biological material represent a serious public health problem, as they put workers at risk of contracting infectious diseases. These incidents can occur through direct contact with contaminated fluids, such as blood or secretions, or through percutaneous and mucosal exposure to potentially infectious materials. Objective: Analyzing data from the São Patrício I and São Patrício II health regions aims not only to understand the epidemiological profile of these accidents, but also to improve prevention strategies. Methodology: This research is descriptive and quantitative, based on the analysis of secondary data on notifications of accidents at work involving exposure to biological material. Data from the Ministry of Health’s Information Technology Department (DataSUS) and the Notifiable Diseases Information System (SINAN) will be used. Results: In order to reduce these risks and ensure a safer working environment, standards such as NR-15 and NR-32 have been implemented, establishing strict guidelines for occupational safety. The Notifiable Diseases Information System (SINAN) plays an essential role in collecting and disseminating data on accidents at work, including those involving exposure to biological materials. This system enables continuous epidemiological monitoring, identifying patterns of occurrence and risk groups, guiding the formulation of effective public policies and the adoption of effective preventive measures. Conclusion: Health professionals are among the most vulnerable groups to this type of accident, a fact that may be related to frequent exposure to biological materials, as well as a possible failure to adhere to biosafety standards. In addition, the inadequate use of Personal Protective Equipment (PPE) such as gloves and masks contributes significantly to the increased risk of contamination.